Chemical profiles, sensory attributes and effect of marinating time on the formation of heterocyclic amines of four types of soy sauce in roasted chicken - Alam Shah, Nur Syifaa (2016)
Soy sauce is a fermented condiment used by many Asian countries due to its salty and distinct tasty taste called umami. As soy sauce has been widely used in Southeast Asian cooking, it is important to well-characterize them based on their chemical compositions. Compounds such as free amino acids and glucose which formed during soy sauce fermentation have significant effects on the flavor and taste of soy sauce. However, these compounds also may act as precursor to increase the formation of heterocyclic amines (HCAs). HCAs are potent mutagens that can be easily form in cooked food and a risk factor for human cancers. The aim of this study was to determine the chemical characteristics and sensory attributes of different types of soy sauce (sweet, salty, light and dark) and their effects as marinating ingredient on the formation of HCAs in roasted chicken. The chemical profiling of four different types of soy sauce which are widely consumed and commercially available in Southeast Asia were determined. Sweet, salty, light and dark soy sauce were discriminated based on their chemical characteristics such as sodium chloride, sugars, organic acids, total nitrogen and free amino acids. Sodium chloride was determined by titration, sugar and organic acid by High Performance Liquid Chromatography (HPLC), free amino acids by Gas Chromatography (GC) and total nitrogen by Kjeldhal method. The sensory attribute was studied using the Quantitative Descriptive Analysis (QDA) and the correlation with chemical profiles was analyzed by orthogonal partial least square discriminant analysis (OPLS-DA). In HCAs analyses, chicken breast samples were marinated with sweet, salty, light and dark soy sauce at 0, 3, 6 and 12 hours. The concentration of free amino acids, sugars and creatinine in marinated samples were determined before roasting while HCA’s concentration were determined in roasted chicken samples. Unmarinated chicken breasts were treated in similar conditions to serve as reference sample. Result showed that sugars (fructose, glucose and sucrose) were found to be dominant compounds in sweet (35.50 - 64.52 g/100 ml), dark (14.19 - 30.73 g/100 ml) and salty soy sauce (7.27 - 21.74 g/100 ml). The sensory attributes such as color, caramel odor, viscosity and sweetness taste has increased the overall acceptance in these types of soy sauce. In light soy sauce, sodium chloride (11.69 - 12.58 g/100 ml), total nitrogen (0.52 - 0.88 g/100 ml) and free amino acids (331.20 - 1053.46 mg/100 ml) appeared to be dominant compounds. It was found that saltiness and umami taste were the important sensory attributes that well-characterized the taste of light soy sauce. In HCAs analyses, results showed that all types of soy sauce significantly increased (p ≤ 0.05) the concentration of HCAs in roasted chicken with increasing marinating time. The highest total concentration of HCAs was found in samples marinated with light soy sauce at 12 hours followed by dark, salty and sweet and the percentage of increment were up to 887%, 375%, 193% and 169% respectively. PhIP showed a complete reduction by 100% in samples marinated with sweet soy sauce at 0 hour. Variations in raw materials used and different production process of different types of soy sauce may contribute to the different chemical profiles and sensory attribute of soy sauce. Free amino acid was found to be strongly correlated with the formation of HCAs than that of reducing sugar and creatinine. The present study suggests that reducing marinating time with soy sauce is important to control the higher formation of HCAs in roasted chicken. Sweet soy sauce could be a better selection of the types of soy sauce to be used as marinating ingredient in the preparation of roasted chicken.